Preparation and characterization of activated montmorillonite clay supported 11-molybdo-vanado-phosphoric acid for cyclohexene oxidation. Issue 9 (24th December 2014) - Boudjema, S.; Vispe, E.; Choukchou-Braham, A.; Mayoral, J. A.; Bachir, R.; Fraile, J. M.
Abstract : Heterogenization of homogenous catalysts consisting of vanadium substituted polyphosphomolybdate with Keggin structure supported on activated bentonite for epoxidation of cyclohexene. Abstract : A new heterogeneous catalyst (PVMo/bentonite), consisting of vanadium substituted polyphosphomolybdate with Keggin structure H4 [PVMo11 O40 ]·13H2 O (PVMo) supported on acid activated bentonite (clay from Hammam Boughrara, Maghnia, Algeria), was prepared by witness impregnation and characterized by X-ray diffraction, BET, Fourier-transformed infrared spectroscopy, 31 P NMR, UV-vis diffuse reflectance spectroscopy and thermogravimetric & differential thermal analysis (TG-DTA). X-ray diffraction indicated that PVMo was properly loaded on bentonite as a support. Heterogenization of homogenous catalysts is really interesting, as heterogeneous catalysts are recoverable. Therefore, the synthesized materials can be used as efficient heterogeneous catalysts for epoxidation of cyclohexene. The obtained results showed that a better catalytic activity can be obtained with PVMo/bentonite (81.5% of conversion), by drop addition of H2 O2, for 3 hours.